SCREENING AND MOLECULAR CHARACTERIZATION OF WHITE ROT FUNGI CAPABLE OF LACCASE PRODUCTION AND DYE DECOLOURIZATION: Life Science-Biology - JEBAPRIYA, G. ROSELINE; GNANADOSS, J. JOEL (International Journal of Life Science and Pharma Research, 2014)
This study describes the isolation of white rot fungi, their molecular characterization and screening for their ability to produce laccase and decolourize the synthetic dyes. Twenty two white rot fungi were isolated from the collected fruiting bodies and screened for their ability to produce laccase. Of these, ten isolates were laccase producers. Among the laccase producing fungi, three isolates namely LCJ155, LCJ164 and LCJ169 were also efficient in synthetic dye decolourization. The three promising isolates were identified by conventional and molecular methods. Fungal DNA was extracted, ITS-rDNA amplified by PCR, and ITS regions were sequenced. Based on the molecular characterization, the novel laccase producing isolates was identified as Pleurotus floridanus LCJ155 (Accession no. KF373566), Leucocoprinus cretaceus LCJ164 (Accession no. KF383135) and Agaricus sp. LCJ169 (Accession no. KF383136). The three isolates LCJ155, LCJ164 and LCJ169 can therefore be used in developing an eco-friendly technology for bioremediation of the dye containing effluents from dyestuff industries.